IMPLEMENTASI UNDANG-UNDANG RI NOMOR 36 TAHUN 2009 TENTANG KESEHATAN DALAM MENINGKATKAN PELAYANAN KESEHATAN DI RSUD KOTA DEPOK - Shafira Lafitri Kurniawan (2022)
The background of writing regarding the implementation of public health services a the Depok City Regional General Hospital, while based on the problems that exist in the field, the purpose of this study is to find out and describe how the implementation of public health services at the Depok City Regional General Hospital. The research method used in this research is descriptive qualitative, research conducted on independent variables without making comparisons or connecting with other variables with the focus of research including communication, resources, attitudes of implementers and bureaucratic structures. Data collection techniques were carried out by conducting in-depth interviews, observation and document research. The key informants in this study were the head of hospital finance and hospital staff while the other informants were outpatients. The results of the study can be concluded that the implementation of public health services at the Depok City General Hospital has been going quite well. Even so, on the other hand, to further support and support the implementation of public health services in the health sector, it is still not enough to further optimize its implementation. Until now the implementation of hospital health services is carried out with existing operational support. Therefore, it needs assistance, both adding dental specialists, adding medical services and improving facilities and infrastructure. To meet the standards based on Law No. 36 of 2009 concerning Health which mandates that quality and equitable health services must continue to be improved.